Polymer nanostructures with templates - Cheang, Ting Wei. (2012)
Templating is one of the most effective techniques in synthesizing one-dimensional polymer nanostructures with tailored dimensions. In this study, Polyvinylidene Fluoride (PVDF) and Poly(vinylidene fluoride-co-trifluoroethylene) (P(VDF-TrFE)) were selected owing to their remarkable properties. Commercial and fabricated porous Anodic Alumina (AAO) templates were utilized to attain the nanostructures.